RX strikes back / Nadia Natasha Johar and Assoc. Prof. Dr. Mahmathi Karuppannan - Johar, Nadia Natasha; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
The highly anticipated event of the semester, Rx Strikes Back, took place on the evening of May 3rd, 2023, marking an exciting moment for students. Organized by the Academic and Innovation Bureau Society of Pharmacy Students (SOPHYS) 2022/2023, the program was held at Dewan Kuliah 500, FF4. The primary objective of Rx Strikes Back was to uplift students' motivation levels as they embarked on a new semester and equip them with effective study strategies to achieve excellent academic results in the current and future semesters. Moreover, the program aimed to provide students with valuable tools to manage stress effectively, enabling them to focus on their studies and acquire knowledge more efficiently.